PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH PADA MATERI GLOBALISASI TERHADAP HASIL BELAJAR SISWA SDN BLANG KIREE - Nurmasyitah Nurmasyitah. (Jurnal Pesona Dasar, 2019)
This research entitled the application of model of learning make a match in the content ofglobalization on student learning outcomes SD Blang Kiree. The problem in this research ishow student learning outcomes by using cooperative learning models make a match in thecontent of globalization on class IV SD Blang Kiree. This research aims to know the results ofthe learning model cooperative learning using make a match. This research uses qualitativeresearch method. The subjects of the research were grade IV SD Blang Kiree totalling 25persons. The conclusion that the application of the model make a match increases studentlearning results in SD Blang Kiree.